Comparison of serum copper, chromium and selenium concentrations in diabetic and nondiabetic population and their association with glycated hemoglobin levels - Shaik Fayazul Haq, Busi Karunanand, Kamla Pati Mishra, Dinesh Kumar Sharma, Ajit Singh (Journal of Applied Pharmaceutical Science, 2021)
Introduction: The microelements are an integral component of glucose homeostasis and other catalytic reactions. Serum concentrations of various micronutrients are associated with glycosylated hemoglobin (HbA1c) levels and complications of diabetes.Methodology: The present study compares the serum concentrations of copper (Cu), chromium (Cr), and selenium (Se) in diabetic patients and nondiabetic control subjects and also investigated the association of serum Cu, Cr, and Se concentrations with HbA1c levels.Results: The study population included 126 cases and 126 controls in a 1:1 ratio with the mean age of 56 years. Auto analyzers analyzed trace elements and HbA1c with the standard procedures. Lipid levels, including total cholesterol, high and low-density lipids, were statistically significantly high in diabetic patients than control subjects (p-value
Keywords: Trace elements, micronutrients, diabetes mellitus, oxidative stress, diabetic complications.